外周血造血干细胞移植治疗侵袭性外周T细胞淋巴瘤41例临床分析 (Zhonghua Xue Ye Xue Za Zhi, 2018)
OBJECTIVE: To evaluate clinical outcomes of autologous and allogeneic peripheral blood stem cell transplantation (PBSCT) for aggressive peripheral T-cell lymphoma (PTCL). METHODS: From June 2007 to June 2017, clinical data of PTCL patients who underwent PBSCT were assessed retrospectively. RESULTS: Among 41 patients, 30 was male, 11 female, and median age was 38(13–57) years old. Seventeen patients with autologous PBSCT (auto-PBSCT) and 24 patients with allogeneic PBSCT (allo-PBSCT) were enrolled in this study. Eight patients (8/17, 47.1%) in auto-PBSCT group were ALK positive anaplastic large cell lymphoma (ALCL), 7 patients (7/24, 29.2%) with NK/T cell lymphoma and 9 patients (9/24, 37.5%) with PTCL-unspecified (PTCL-U) in allo-PBSCT group (P=0.035). There were 58.8% patients (10/17) in complete response (CR) status and 11.8% (2/17) in progression disease (PD) status before transplantation in auto-PBSCT group, and 8.3% (2/24) in CR status and 45.8% (11/24) in PD status before transplantation in allo-PBSCT group (P=0.026). The 2-years cumulative overall survival (OS) were (64.0±10.8)% and (53.5±9.7)% for auto-PBSCT and allo-PBSCT respectively (P=0.543). The 2-years cumulative disease-free survival (DFS) were (57.1±12.4)% and (53.5±10.6)% for auto-PBSCT and allo-PBSCT respectively (P=0.701). In patients with dead outcomes after PBSCT, 83.3% (5/6) of death cause was relapse in auto-PBSCT and 41.7% (5/12) of death cause was relapse in allo-PBSCT. CONCLUSION: Both auto-PBSCT and allo-PBSCT were effective for PTCL. Allo-PBSCT maybe was better than auto-PBSCT for high-risk PTCL with poor prognosis.